(3EOGQI GdJfhY GdKbGaj aj GdehGQO GdHTQjI (B/s - (3MehOI, YHO GdfGUQ eMeO Ydjs ((3GdbGgQI(B: s (3GdefXeI GdYQHjI ddJfejI GdEOGQjI(B, s, 2005)
(3GdYhdeI hGfJbGd YfGUQ GdEfJGL(B- (3GdefXhQ GdEbJUGOj dEfJbGd YfGUQ GdEfJGL(B- (3hGbY GfJbGd YfGUQ GdEfJGL(B- (3BKGQ GfJbGd GdehQO GdHTQj(B- (3GdKbGaI hGdJfhY GdKbGaj(B- (3GdJfhY GdKbGaj Mhd bjeI GdYed hOhGaYg(B- (3JfhY GdJhGUd Hjf GdGaQGO(B- (3GdJfhY Mhd GdYed GdLeGYj(B- (3JfhY GdGfTWI(B- (3GdCfeGW GdbjGOjI(B- (3hVY GSJQGJjLjI GdehGQO GdHTQjI GdOhdjI(B- (3JfajP GSJQGJjLjI GdehGQO GdHTQjI GdOhdjI(B- (3JbSje GSJQGJjLjI GdehGQO GdHTQjI GdOhdjIs
Keywords: (3EOGQI GdehGQO GdHTQjIs; (3GdYhdeIs